GHOST IN MY SUITCASE - BATES, VANESSA (ADAPT) (CURRENCY Press, 2020)
Twelve-year-old Celeste--'half French, half Chinese and all Australian'--travels to China to scatter her mother's ashes. There she meets her grandmother, Por Por, a quirky and wise woman with an unusual skill. Por Por is a ghost-hunter and her services are much in demand. When Celeste learns she may have inherited her grandmother's talent, she must decide whether to acknowledge her gifts and use them to save her family and friends--and if she has the strength needed for the job.